Podcast Karni Ilyas Club Speech Act Analysis In Mirna Salihin's Cyanide Coffee Case - Christina Natalina Saragih; Dewi Maya Manurung (Jurnal Ilmu Sosial Mamangan, 2024)
This research aims to describe the types of speech acts that found in interviews between Mr Kardi Ilyas and Mr Edi Darmawan Salihin. The research method used was descriptive qualitative research. The data source for this research was obtained from the Kardi Ilyas Club YouTube account which was released on October 7 2023 with a video duration of 1:07:32 seconds. The data in this research were all forms of speech that contain the types of illocutionary speech acts found in the interview between Mr. Karni Ilyas and Mr. Edi Darmawan Salihin. Based on data analysis, it was found that there were five types of illocutionary speech acts obtained, including speech acts. assertive, namely Mr. Edi Darmawan Salihin answered questions asked by Mr. Karni Ilyas and revealed several facts which he thought could be proven to be true as well as providing views and opinions. Furthermore, there are directive speech acts, namely Mr. Edi Salihin also gives many words asking listeners not to witness or watch what he thinks is not appropriate to watch, declarative speech acts, namely speech mocking or swearing at one party who says that they are the perpetrators of the murder. That's not wrong, then the commissive speech act, giving several promises that Mr. Edi Darmawan Salihin will carry out in the future, as well as the expressive speech act, namely conveying his joy or happiness that the perpetrator could also be caught in the law.